Prognostic Impact of Tumor Extension in Patients With Advanced Temporal Bone Squamous Cell Carcinoma - Komune, Noritaka; Miyazaki, Masaru; Sato, Kuniaki; Sagiyama, Koji; Hiwatashi, Akio; Hongo, Takahiro; Koike, Kensuke; Noda, Teppei; Uchi, Ryutaro; Kogo, Ryunosuke; Akagi Tsuchihashi, Nana; Masuda, Shogo; et al. (Frontiers in Oncology, 2020)
Objective: The extreme rarity of temporal bone squamous cell carcinoma (TB-SCC) has delayed the accumulation of high-quality clinical evidence. Our objective here was to explore anatomical factors associated with the prognosis of T4 TB-SCC cases. Study Design: Case series with chart review. Setting: Two academic tertiary care medical center. Subjects and Methods: The medical records of all TB-SCC cases were retrospectively reviewed in two institutions. The resulting dataset contained 30 cases of primary T4 cancer eligible for initial definitive (curative) treatment. Disease-specific survival was calculated according to the Kaplan–Meier method. Cox proportional-hazards model was used to identify anatomical prognosis factors. Results: The disease-specific five-year survival rate of 30 cases of T4 TB-SCC was 53.9 %. The tumor invasion to pterygoid muscle, the posterior fossa dura, sigmoid sinus and destruction of the ossicles were associated with poor prognosis in Univariate analysis. The Multivariate analysis reveal that the invasion of the ossicles, posterior fossa dura and sigmoid sinus are independent prognostic factors (HR: 4.528 [95% CI:1.161-17.658, p=0,030, HR: 5.135 [95% CI:1.616-16.315, p=0,006, HR: 4.292 [95% CI:1.385-13.303, p=0,012). The invasion of the carotid canal, petrous apex, middle fossa dura, otic capsule, pterygoid muscle and middle ear had high hazard ratio (HR>2). The more invaded anatomical factors present in patients resulted in a poorer patient disease specific prognosis, with a statistically significant difference. Conclusions: Assessing which anatomical structures are susceptible to invasion by tumors may be important for predicting TB-SCC patient prognosis and selecting appropriate treatment planning, especially surgical intervention. In addition to previously reported factors, the destruction of the ossicles in the middle ear cavity can be an anatomical prognosis factor.